Investigation of the Effect of Steel Plate Size and Elevated Temperature on Critical Load in Stability Tests - O.A. Pashkov, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents the results of a study of the effect of epoxy-polyester-based powder coatings on the critical strength of plate samples made of rolled sheet steel. The results obtained show that the model using flat elements gives a more accurate result than the model using three-dimensional elements. The best agreement with the experiment was shown by the results obtained in Ansys using the Eigenvalue bucling function, less than 1%. The worst agreement with the experiment was shown by the results obtained in Ansys using Solid elements, about 70%.